PENGARUH MODAL SOSIAL DAN SELF-EFFICACY TERHADAP KINERJA GURU DENGAN MEDIASI KOMITMEN ORGANISASIONAL - Mulyadi, Mulyadi (Students Journal of Economic and Management, 2012)
Teacher qualities often spoken in Indonesia in this decade. That is why need a factual study hits teacher condition and variable that influence the performance. This research is done to test teacher social capital variable influence and self-efficacy teacher towards teacher performance with mediasi commitment organizational school. This research use explains and expand previous research hits social capital influence and self-efficacy towards teacher performance with commitment mediation organizational. Population in this research entire teachers junior high school country at essence regency with sample 206 respondents. Sample taking by using random proportional technics sampling. Data processing by using spss 16.0. This research is done in one period in the year 2012. Analysis method uses doubled regression. The Result shows that: (1) positive influential social capital but not significant towards commitment organisasional, (2) self-efficacy negative influential but significant towards commitment organisasional, (3) negative influential social capital and not significant towards teacher performance, (4) self-efficacy doesnt has positive influence and not significant towards teacher performance, (5) commitment organisasional positive influential and significant towards teacher performance. Social capital variable influence towards teacher performance effectiveer has direct and unnecessary mediasi commitment variable organisasional. Variable influence self-efficacy effectiveer has not directed so those need mediasi commitment variable organizational. KeywordÂ : Teacherâs social capital, Teacherâs Self-efficacy , commitment organizational, Teacherâs performance